Frequency-resolved photoconductivity studies in amorphous chalcogenide films - Akat, Ercüment. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2000., 2000)
Frequency-resolved photocurrent measurements (FRPC) were carried out on amorphous chalcogenide films such as AsSeSb AsSe and AsSeTe, by a method called frequency-resolved spectroscopy (FRS) as a function of temperature (between 230 K and 395 K), of excitation intensity (between 40 and 600 ) and in the frequency range of 10 Hz to 1.1x104 Hz, yielding the lifetime distribution directly. The results indicate that the recombination is through distant pairs, since the lifetime does depend on the excitation intensity, through ; as at 295 K and at 395 K, rather than by geminate (twin) pairs. It can also be concluded that there is a continuous distribution of states in the mobility gap implied by the value of the exponent 0.72 (in ), which is between 0.5 and 1.0, the figures that according to Rose (1978), correspond respectively to monomolecular and bimolecular recombination. The temperature exponent in the relationship has turned out to be between 7 and 10 for a frequency of some (=200 Hz); and 11 and 13 for (=3322 Hz); the value of the exponent showing a diminishing behaviour as the generation rate (intensity of excitation) is elevated. Finally, the exponent in the relationship is found to depend on both temperature and the generation rate in a manner such that the photocurrent will be more sensitive (inversely) to the frequency of excitation as either one of the above variables or both are lowered.
Keywords: Photoconductivity.; Chalcogenides.; Amorphous substances.